ISCHEMIC HEART DISEASE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Ischemic heart disease (IHD), also known as coronary artery disease (CAD), is one of the leading causes of morbidity and mortality worldwide. It occurs due to the narrowing or blockage of coronary arteries, reducing blood flow to the myocardium. This article discusses the pathogenesis, risk factors, clinical manifestations, diagnostic methods, and modern approaches to treatment and prevention of IHD.